The Role of Intra-Clutch Variation of Magpie Clutches in Foreign Egg Rejection Depends on the Egg Trait Considered - Molina-Morales, Mercedes; Gómez, Jesús; Liñán-Cembrano, Gustavo; Precioso, Marta; Martínez, Juan G.; Avilés, Jesús M. (Frontiers in Ecology and Evolution, 2021)
The existence of a coevolutionary process between avian brood parasites and their hosts predicts a lower intra-clutch variation in egg appearance of host eggs among rejecters as this would favour egg discrimination of parasite eggs by hosts once parasitic egg mimicry had evolved. So far empirical tests of this prediction have ignored the fact that different aspects of host egg phenotypes may differ in the relative role of environmental versus genetic determination, and hence that the role of intra-clutch variation in egg rejection within a population cannot be invariant. Here, we estimated whether the intra-clutch variation in several aspects of host eggshell features is consistently associated to rejection of parasitic foreign eggs across years in a magpie host population parasitized by great spotted cuckoos. We innovatively estimated spottiness by means of the fractal dimension of eggs, which considers the homogeneity of spot pattern complexity in eggshells. Our results show that low intra-clutch variation in the blue-green coloration at the middle area of the eggs associated with a high chance of rejection, but only in one of the three years we conducted the study. In addition, females that rejected foreign eggs presented more homogenous spot patterns in their clutches as estimated by their fractal dimension than females that accepted experimental eggs, independently of the year of study. Finally, intra-clutch variation in egg volume of host eggs was not associated to rejection. Analyses at the individual level revealed that the relative role of genetic versus environmental factors determination egg phenotype would be feature-specific in magpies, females having a characteristic spottiness, but not colour or volume, pattern. Our work stresses the importance of considering a holistic approach including several aspects of variation in host egg phenotype (size, colour, and homogeneity of spot pattern), as some aspects might be more susceptible to selection through egg rejection than others, presumably because they are less influenced by variation in the environmental conditions. Moreover, our study highlights the importance of replication in studies on the adaptive value of host traits in egg rejection.